Higher education teachers' descriptions of their own learning: a large-scale study of Finnish Universities of Applied Sciences - Töytäri, Aija; Piirainen, Arja; Tynjälä, Päivi; Vanhanen-Nuutinen, Liisa; Mäki, Kimmo; Ilves, Vesa (Higher education research and development, 2016)
In this large-scale study, higher education teachers' descriptions of their own learning were examined with qualitative analysis involving application of principles of phenomenographic research. This study is unique: it is unusual to use large-scale data in qualitative studies. The data were collected through an e-mail survey sent to 5960 teachers at universities of applied sciences in Finland. The number of respondents was 1622. Four hierarchically structured categories of learning were found: individual learning, collegial learning, team learning and innovative partnership learning. The role of teachers in higher education demands innovative partnership learning: being active at the societal level with workplaces and international partners.